Pregnancy coercion and partner knowledge of contraceptive use among Ethiopian women - Jessica L. Dozier; Linnea A. Zimmerman; Bedilu A. Ejigu; Solomon Shiferaw; Assefa Seme; Mahari Yihdego; Robel Yirgu; Shannon N. Wood (Elsevier, 2022)
Objective: To examine the relationship between pregnancy coercion and partner knowledge of contraceptive use. Study design: Cross-sectional Performance Monitoring for Action-Ethiopia data were collected in October-November 2019 from a nationally representative sample of women ages 15 to 49. The analytical sample (n = 2,469) included partnered women using contraception in the past year. We used multinomial logistic regression to examine associations between past-year pregnancy coercion (none, less severe, more severe) and partner knowledge/couple discussion of contraceptive use (overt use with couple discussion before method initiation (reference group), overt use with discussion after method initiation, and covert use of contraception). Results: Most women reported their partner knew they were using contraception and had discussed use prior to method initiation (1,837/2,469, 75%); 16% used overtly and discussed use after method initiation, and 7% used contraception covertly. The proportion of covert users increased with pregnancy coercion severity (4%none, 14%less severe, 31%more severe), as did the proportion of overt users who delayed couple contraceptive discussions, (14%none, 23%less severe, 26% more severe); however, overt use with couple discussion before method initiation decreased with pregnancy coercion severity (79%none, 60%less severe, 40%more severe). The risk of covert use among women experiencing less severe pregnancy coercion was four times greater than women who experienced no pregnancy coercion (adjusted relative risk ratio, (aRRR) = 3.95, 95% confidence interval (CI) 2.20-7.09) and ten times greater for women who experienced the most severe pregnancy coercion (aRRR = 10.42, 95% CI 6.14-17.71). The risk of overt use with delayed couple discussion also increased two-fold among women who experienced pregnancy coercion compared to those who did not (less severe aRRR = 2.05, 95% CI 1.39-2.99; more severe aRRR = 2.89, 95% CI 1.76-4.73). Conclusion: When experiencing pregnancy coercion, women may avoid or delay contraceptive conversations with their partners. Increased pregnancy coercion severity has the greatest association with covert use and couple contraceptive discussions. Implications: The presence and timing of couple discussions about contraception are critical for ensuring safety for women experiencing pregnancy coercion. Screening for pregnancy coercion must be included within contraceptive counseling so that women can choose methods that maximize their reproductive autonomy.